KESALEHAN MUALAF DALAM BINGKAI KEISLAMAN - Zainap Hartati (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2019)
The development of converts in Central Kalimantan is quite widespread in several districts/cities, but its existence still needs a joint commitment to foster and guide the understanding and guidance of religion in the strict teachings of Islam. Based on this matter, this research was carried out with the formulation of how piety when they convert to Muslim, with the aim of analyzing the piety of converts in their Islamic practices in Central Kalimantan. The method used in this research is interviews, observation and documentation. The results obtained that the piety of converts as a Muslim appears in routine activities such as prayer and fasting which are still immature understood and actualized in daily life. Their motivation to become a Muslim is more dominant because of marriage, but there are many factors that characterized Islam, such as the family environment, the surrounding community and their motivation to convince their faith in Islam as their religion.